The Role of Erythropoietin in Preventing Anemia in the Premature Neonate - Oana Cristina Costescu; Eugen Radu Boia; Marioara Boia; Daniela Mariana Cioboata; Florina Marinela Doandes; Nicoleta Lungu; Mihai Dinu; Emil Radu Iacob; Aniko Maria Manea (MDPI AG, 2023)
Recombinant human erythropoietin (rhEPO) treatment is an alternative to red blood cell (RBC) transfusions in neonates presenting anemia of prematurity (AOP). This study assesses the impact of early rhEPO administration on AOP (any stage) incidence, as well as the incidence of individual AOP stages and RBC transfusions. Out of 108 preterm neonates, 49 were administered rhEPO and compared to the remaining group using univariate and multivariate analyses. Univariately, gestational age (GA), birth weight (BW), hemoglobin (Hb), hematocrit (HCT), RBC levels, and iron administration were significantly associated with AOP (p < 0.05 each); however, only the latter remained significant following multivariate analysis (AOR: 2.75, 95% CI, 1.06-7.11). Multinomial analysis revealed rhEPO treatment was associated with a near three-fold reduction in moderate AOP incidence (OR: 0.36, 95% CI, 0.15-0.89). Furthermore, ANCOVA revealed positive correlations between rhEPO administration and 21-day Hb (p < 0.01), HCT (p < 0.05), and EPO (p < 0.001) levels. The results confirm previously reported benefits of rhEPO treatment, such as reduced moderate AOP incidence and increased Hb, HCT, and serum EPO levels.